Non-invasive cardiac stress studies may not offer significant benefit in pre-kidney transplant evaluation: A retrospective cohort study. - Durga Anil K Kanigicherla; Talvinder Bhogal; Katie Stocking; Rajkumar Chinnadurai; Simon Gray; Saad Javed; Christien Fortune; Titus Augustine; Philip A Kalra (PLoS ONE, 2020)
Background Screening with cardiac non-invasive stress studies (NISS) prior to listing for kidney transplantation can help in identifying treatable coronary disease and is considered an integral part of pre-kidney transplant evaluation. However, few studies assessed their effectiveness in all patients evaluated for transplantation in clinical practice. To evaluate the role of NISS in pre-kidney transplant evaluation we analyzed their impact prior to waitlisting in 1053 adult CKD-5 patients consecutively evaluated in Greater Manchester, UK during a 6-year period. Methods 918 waitlisted patients were grouped based on presence or absence of Diabetes or Cardio-Vascular Disease (CVD): Group-1 (255 DM-/CVD-/NISS-), Group-2 (368 DM-/CVD-/NISS+) and Group-3 (295 with DM or CVD). Results Group-2 patients had longer 'time-to-listing' (5.5months in Group-1 vs 6.9months in 'Normal-NISS' vs 9.9months in 'Abnormal-NISS', p<0.01) but none with 'Abnormal-NISS' needed coronary revascularization before listing. NISS was followed by revascularization in 8 Group-3 patients (3%). In multi-variate analyses, there was no association of NISS on death or MACE in listed patients. During follow up, Transplantation was the most significant factor associated with improved outcomes in all subgroups (HR:0.97, p<0.001). 135 patients were considered unsuitable for waitlisting, with NISS influencing management in 11 of these patients (8%). Conclusions Pre-kidney transplant evaluation with NISS influenced clinical management in 19 of 1053 (2%) patients. Screening with NISS added limited benefit but contributes to significant delays in listing and adding resource implications. Further studies are needed to assess clinical and cost effectiveness of NISS in pretransplant evaluation to optimize outcomes and resources.